State-of-the-art methods of qualitative and quantitative assessment of eye microcirculation - T. N. Kiseleva; S. Yu. Petrov; T. D. Okhotsimskaya; O. I. Markelova (Российский офтальмологический журнал, 2023)
Circulatory disorders in eye vessels play an important role in the development of ophthalmic pathologies, in particular socially significant diseases such as glaucoma, age-related macular degeneration, diabetic retinopathy, and retinal vascular occlusion. Eye hemodynamics features are an important diagnostic criterion for both ocular and systemic diseases. A comprehensive assessment of blood flow in various structures of the eyeball offers additional information on the pathogenesis of the diseases and helps develop new approaches to monitoring the effectiveness of treatment and vascular pathology prognostication. Thanks to the improved technologies, we have today a variety of invasive and non-invasive techniques for examining ocular hemoperfusion, including those intended for retrobulbar blood flow and intraocular blood circulation evaluation. The review article is focused on the state-of-the-art techniques: fluorescein angiography, ultrasound examination involving blood flow assessment by colour Doppler mapping and Dopplerography, optical coherence tomography in the angiographic mode and laser speckle flowgraphy. The role of these techniques in the diagnosis of vascular pathology and their advantages and disadvantages when used in ophthalmological practice is considered.